Victims of environmental harm: rights, recognition and redress under national and international law - Hall, Matthew (Routledge frontiers of criminal justice, 2013)
Victims, environmental harm and international law -- Identifying and conceptualising the victims of environmental harm -- Environmental victims across jurisdictions : criminal law and state responsibility -- Human rights, victim rights, environmental rights? -- Responding to environmental victimisation : compensation, restitution and redress -- Mapping out a green victimology